Preparation of canine C‐reactive protein serum reference material: A feasibility study. (25th March 2018) - Canalias, Francesca; Piñeiro, Matilde; Pato, Raquel; Peña, Raquel; Bosch, Lluís; Soler, Lourdes; García, Natalia; Lampreave, Fermín; Saco, Yolanda; Bassols, Anna
Abstract : Background: The availability of a species‐specific reference material is essential for the harmonization of results obtained in different laboratories by different methods. Objectives: We describe the preparation of a canine C‐reactive protein (cCRP) serum reference material containing purified cCRP stabilized in a serum matrix. The material can be used by manufacturers to assign values to their calibrator and control materials. Methods: The serum matrix was obtained using blood collected from healthy dogs, stabilized and submitted for a delipidation process. The reference material was prepared by diluting purified cCRP in the serum matrix containing 1.0 mol/L HEPES buffer, 3.0 mmol/L calcium chloride, 80, 000 kUI/L aprotinin, and 1.0 mmol/L benzamidine hydrochloride monohydrate at a pH of 7.2, and dispensing (0.5 mL) the matrix into vials that were then frozen. Results: The pilot batch of 200 vials was shown to be homogeneous and stable after a stability study at various temperatures and over a total time of 110 days. The prepared material was submitted to an assignment value study. Eight laboratories from different European countries participated by using the same reagents for an immunoturbidimetric method adapted for different analyzers. The obtained cCRP concentration in the reference material was 78.5 mg/L with an expanded uncertainty ( k = 2) of 4.2 mg/L. Conclusions: Canine C‐reactive protein serum reference material has been produced that allows harmonization of results obtained by different methods and different laboratories, thus reducing the possibility of errors and misunderstandings.